Creating blue oceans for the future - Abd Razak, Dzulkifli (2008)
INTELLECTUAL renaissance is the main takehome message that came from Deputy Prime Minister Datuk Seri Najib Razak's opening address at the Blue Ocean Strategy (BOS) seminar on education and training held recently. This was contextualised within Malaysia's unique position in the intellectual world, based on at least six wideranging dimensions: First is the rich, indigenous and diverse Malay archipelago that reaches out to no less than 500 million people of the Malayspeaking world. Indeed, in terms of numbers alone, it puts Malaybased language among the most widely spoken languages in the world. This is certainly one uniqueness that Malaysia could harness for itself as part of the BOS.